'We are not the virus'-Experiences of racism among East & Southeast Asian heritage young people in London during the height of the COVID-19 pandemic. - Lu Gram; Ada Mau (PLOS Global Public Health)
The spread of COVID-19 was accompanied by news reports of surging racism, xenophobia, and hate crime all over the Global North targeting individuals of East and Southeast Asian (ESEA) descent. However, little empirical research has documented the impacts of COVID-19 on child and adolescent ESEAs. We describe and analyse the mental health experiences of young ESEA Londoners during the height of the COVID-19 pandemic. We purposively recruited 23 young people (aged 9-20) of ESEA heritage through social media and existing ESEA networks and analysed transcripts using thematic analysis. Participants experienced distress from being exposed to multiple forms of racism ranging from strangers on the street avoiding or harassing them to classmates at school or university making racist 'jokes', comments or 'banter'. Participants worried about hate crimes reported in news media and experienced anxiety from seeing pervasive racist content in online social media. Some participants responded by physically isolating themselves at home for long periods, whilst others chose to participate in activism, providing a sense of agency. Action by parents and school authorities was reported to help prevent further bullying, but respondents did not always feel able to approach these for help. Our findings put into focus the strain on young ESEA Londoners' mental health caused by COVID-related racism and jar against simplified depictions of metropolitan places, such as London, as centres of cosmopolitanism and tolerance. To promote the emotional wellbeing of young ESEAs, future policy should facilitate action by schools and universities against anti-ESEA racism and support ESEA community-building efforts to enhance resilience in the face of racism.